Optimizing treatment for metastatic renal cell carcinoma. Issue 12 (December 2011) - Patard, Jean-Jacques; Porta, Camillo; Wagstaff, John; Gschwend, Juergen E
With the advent of targeted antiangiogenic therapies for renal cell carcinoma (RCC), the prognosis for patients with locally advanced or metastatic disease has significantly improved. Indeed, the results of several randomized clinical trials have demonstrated that targeted therapies, such as tyrosine kinase inhibitors (TKIs), provide superior efficacy and tolerability compared with traditional cytokine-based treatments. However, TKI therapy is still associated with significant toxicities related to off-target inhibition that are detrimental to patient quality of life. The results of ongoing head-to-head trials will determine how these agents compare with each other in terms of efficacy, and whether TKIs that interact with fewer off-target kinases have improved tolerability profiles. Furthermore, examining how these agents could be integrated with surgery to provide a multimodal approach to the treatment of metastatic RCC could further improve the outlook for RCC patients.